2018
DOI: 10.1002/2017ja024872
|View full text |Cite
|
Sign up to set email alerts
|

Jovian Auroral Ion Precipitation: Field‐Aligned Currents and Ultraviolet Emissions

Abstract: A model is described for the transport of magnetospheric oxygen ions with low charge state and energies up to several MeV/nucleon (MeV/u) as they precipitate into Jupiter's polar atmosphere. A revised and updated hybrid Monte Carlo model originally developed by Ozak et al. (2010, https://doi.org/10.1029/2010JA015635) is used to model the Jovian X‐ray aurora. The current model uses a wide range of incident oxygen ion energies (10 keV/u to 5 MeV/u) and the most up‐to‐date collision cross sections. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 84 publications
(145 reference statements)
1
24
0
Order By: Relevance
“…These charge states are sufficiently reached for both species at an energy between 200 and 300 keV/u, where they become the most probable charge state for the given energy (a total energy of 3.2 and 6.4 MeV for oxygen and sulfur, respectively). These newly developed equilibrium fractions supersede previous models presented by Ozak et al () and Houston et al (), which showed an O 6+ peak at nearly 1 MeV/u and an S 6+ peak at 600 keV/u.…”
Section: Physical Processes and Model Descriptionsupporting
confidence: 83%
See 4 more Smart Citations
“…These charge states are sufficiently reached for both species at an energy between 200 and 300 keV/u, where they become the most probable charge state for the given energy (a total energy of 3.2 and 6.4 MeV for oxygen and sulfur, respectively). These newly developed equilibrium fractions supersede previous models presented by Ozak et al () and Houston et al (), which showed an O 6+ peak at nearly 1 MeV/u and an S 6+ peak at 600 keV/u.…”
Section: Physical Processes and Model Descriptionsupporting
confidence: 83%
“…Hence, X‐ray observation can be used to estimate heavy ion fluxes with energies in excess of 200 keV/u (i.e., 3 MeV and higher) and to determine the morphology of this precipitation made over the polar caps. Such precipitation has been shown to be associated with downward field‐aligned currents, both due to the primary ion precipitation and the resultant secondary electron escape from the atmosphere (Cravens et al, ; Houston et al, ; Ozak et al, ; Ozak et al, ). The ion precipitation is also responsible as a source of ionization in the thermosphere, which was explored further in the earlier model presented by Houston et al ().…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations